(untitled) (Bangladesh Journal of Nuclear Medicine, 2023)
Ewing’s sarcoma (ES) is a bone-related tumor that typically affects young children and adolescents. Primary renal Ewing sarcoma (RES) is extremely rare. Sources of Ewing sarcoma in the kidney include invagination or migration of neural crest cells to the kidney. Here, a case of a young adult male with renal Ewing sarcoma is presented. A 28-year-old male presented with nausea, hematuria, and left flank pain for seven days with an unremarkable previous medical history. An ultrasound and CT scan revealed a massive lobulated mass in the upper and midsection of the left kidney. A radical nephrectomy was done. Histopathology and immunohistochemistry revealed Ewing’s sarcoma/primitive neuroectodermal tumor. The chest X-ray and chest CT scan were negative for metastasis. Initial staging was T2bNxM0. Before starting further treatment, the patient was advised to undergo a fluorine-18 FDG (fluorodeoxyglucose) positron emission tomography (F-18 FDG PET-CT) scan for the detection of occult metastases. A F-18 FDG PET-CT scan revealed peritoneal seeding, skeletal and abdominal lymph node metastases. A multimodality workup is essential for proper management of Ewing sarcoma of the kidney due to its rarity and unusual location. F-18 FDG PET-CT plays a critical role in the detection of occult metastases, staging, restaging, and treatment planning in patients with RES. Bangladesh J. Nuclear Med. 26(1): 54-57, 2023